2016
DOI: 10.1021/acsami.5b11286
|View full text |Cite
|
Sign up to set email alerts
|

Novel Surface Passivation Technique for Low-Temperature Solution-Processed Perovskite PV Cells

Abstract: Low-temperature solution-processed perovskite solar cells are attracting immense interest due to their ease of fabrication and potential for mass production on flexible substrates. However, the unfavorable surface properties of planar substrates often lead to large variations in perovskite crystal size and weak charge extractions at interfaces, resulting in inferior performance. Here, we report the improved performance, reproducibility, and high stability of "p-i-n" planar heterojunction perovskite solar cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 43 publications
1
61
0
3
Order By: Relevance
“…It is obvious that MB 1.5 modified device exhibits a higher V oc than the control device under different light intensities (Figure 2e). [48,49] Furthermore, the dark current density of MB 1.5 modified device is shown in Figure 2f. [46] The slope values of 1.52 k B T/e and 1.29 k B T/e are obtained for the control and MB 1.5 modified devices, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…It is obvious that MB 1.5 modified device exhibits a higher V oc than the control device under different light intensities (Figure 2e). [48,49] Furthermore, the dark current density of MB 1.5 modified device is shown in Figure 2f. [46] The slope values of 1.52 k B T/e and 1.29 k B T/e are obtained for the control and MB 1.5 modified devices, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…After cleaning the surface of the NiO x layer, the perovskite and PCBM layers were prepared and deposited as reported. 14,17,18 After Ag deposition, the devices were sealed by a glass plate. The current density-voltage (J-V ) characteristics was measured by a solar simulator system (Asahi Spectra Co. Ltd., California, USA).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Planar type perovskite solar cells have been developed to circumvent the complicated analysis of perovskite semiconductor in mesoporous structure, and to produce the perovskite solar cells via lower temperature processes. [7][8][9][10][11][12][13][14][15][16][17][18] We have demonstrated that the solar cells consisting of Tin-doped indium oxide (ITO)/Poly (3,4-ethylenedioxythiophene): Poly(styrenesulfonate) (PEDOT:PSS)/Perovskite/Phenyl-C61-Butyric-Acid-Methyl Ester (PCBM)/Ag ( Fig. 1) have the ideal diode properties and high reproducibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the device with SAED exhibits a larger R reb (264.8 Ω cm 2 ) than that of the control device (219.2 Ω cm 2 ) measured under dark conditions. [37][38][39] It should be highlighted that SAED film thickness is critical to PSC device performance. [32] Similar results were also obtained for 0 bias tests.…”
Section: Resultsmentioning
confidence: 99%